Microsoft Office 2007 - Bruzzese, J. Peter; Safari eBooks ([Indianapolis, Ind.] : Que, 2008)
"You've got Microsoft Office 2007...now get the most out of it, faster and more easily than ever before! In 50 quick video lessons, J. Peter Bruzzese shows you all you need to maximize your productivity with Office 2007's best tools and shortcuts, and its brand-new ribbon interface! Microsoft Office 2007 teaches Office 2007's most sophisticated features and techniques visually: just watch! You'll master high-powered Office 2007 skills at your own pace--and get specific answers and solutions immediately, whenever you need them! These practical videos simplify powerful Office 2007 features like Word mail merges, blog editing, and document encryption...Excel PivotTables, conditional formatting, and automatic data entry...SmartArt and PowerPoint slide masters...Outlook's new To-Do Bar and RSS feeds...and plenty more!"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed March 5, 2009).
Electronic reproduction.
Keywords: Microsoft Office; Electronic books